Thiamine-modified metabolic reprogramming of human pluripotent stem cell-derived cardiomyocyte under space microgravity - Xinglong Han; Lina Qu; Miao Yu; Lingqun Ye; Liujia Shi; Guangfu Ye; Jingsi Yang; Yaning Wang; Hao Fan; Yong Wang; Yingjun Tan; Chunyan Wang; et al. (Signal Transduction and Targeted Therapy, 2024)
Abstract During spaceflight, the cardiovascular system undergoes remarkable adaptation to microgravity and faces the risk of cardiac remodeling. Therefore, the effects and mechanisms of microgravity on cardiac morphology, physiology, metabolism, and cellular biology need to be further investigated. Since China started constructing the China Space Station (CSS) in 2021, we have taken advantage of the Shenzhou-13 capsule to send human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs) to the Tianhe core module of the CSS. In this study, hPSC-CMs subjected to space microgravity showed decreased beating rate and abnormal intracellular calcium cycling. Metabolomic and transcriptomic analyses revealed a battery of metabolic remodeling of hPSC-CMs in spaceflight, especially thiamine metabolism. The microgravity condition blocked the thiamine intake in hPSC-CMs. The decline of thiamine utilization under microgravity or by its antagonistic analog amprolium affected the process of the tricarboxylic acid cycle. It decreased ATP production, which led to cytoskeletal remodeling and calcium homeostasis imbalance in hPSC-CMs. More importantly, in vitro and in vivo studies suggest that thiamine supplementation could reverse the adaptive changes induced by simulated microgravity. This study represents the first astrobiological study on the China Space Station and lays a solid foundation for further aerospace biomedical research. These data indicate that intervention of thiamine-modified metabolic reprogramming in human cardiomyocytes during spaceflight might be a feasible countermeasure against microgravity.